A study of different clinical and biochemical parameters in polycystic ovary syndrome affecting ovulation induction outcome and fertility potential - Siebert, T. I. (Stellenbosch : Stellenbosch University, 2008)
Thesis (DMed (Obstetrics and Gynaecology))--Stellenbosch University, 2008.